Síntese e caracterização de um novo co-amorfo de clorpropamida com a trometamina - VIEIRA JÚNIOR, Francisco Tauvânio (2017)
Chlorpropamide (CLP) is an oral antidiabetic agent used to control blood glucose in patients with Type II Diabetes Mellitus (DMII). CLP has high membrane permeability and low aqueous solubility, which contributes to the reduction of its therapeutic efficacy. The synthesis of co-amorphous drugs is a way to increase aqueous solubility and hence its bioavailability. Thus, this work aimed to synthesize and characterize a new CLP coamorphous, using tromethamine (TRIS) as coformer. The synthesis of this co-amorphous CLP-TRIS (1:1) was performed by the suspension method. in the following, the synthetized material was characterized by X-ray powder diffraction (XRDP), Raman Spectroscopy, Differential Scanning Calorimetry (DSC), Fourier Transform Infrared Spectroscopy (FTIR) and Near Infrared Spectroscopy (NIR). In addition, the aqueous solubility test of the CLP and its co-amorphous was performed to compare the obtained results. The XRDP analysis of the sample synthesized in this study showed the formation of an amorphous phase, presenting a diffraction pattern different from those presented by the crystalline starting compounds (CLP and TRIS) besides showing a good physical stability of this material. The Raman spectra of the co-amorphous also showed spectral differences when compared to those obtained from the starting compounds, such as band disappearance and the (SO) downshift of the CLP and (NH2) of the TRIS bands evidencing the participation of these groups in the interaction between CLP and TRIS. From the FTIR analysis of CLP, TRIS and CLP-TRIS, it was possible to observe that the co-amorphous spectrum presented differences as compared to the CLP and TRIS spectra, such as the occurrence of OH band displaced to a region of lower wavenumber and the reduction of intensity of some bands associated with the NH group, these being possible sites of intermolecular interaction between CLP and TRIS. From the NIR analysis it was possible to observe that the co-amorphous spectrum presented broader bands when compared to the spectra of the forming compounds. In addition, it was observed the appearance of a band of third overtones NH, this being a possible site of intermolecular interaction. DSC analysis between the starting and co-amorphous compounds showed that the latter exhibited significantly different thermal properties of CLP and TRIS, as this material exhibited endothermic events at temperatures below the melting temperatures of its starting compounds. Aqueous solubility assays of CLP-TRIS (1: 1) showed that this new material was about eleven times more soluble than CLP. Thus, probably the new material synthesized in this study will favor the increase in the bioavailability of CLP and10 increase its therapeutic efficacy in the treatment of DMII.